Oral Presentation to Improve the Students’ Speaking Skill of the Seventh Grade Students at SMPN 35 Surabaya - Laely Vitriyati (STKIP PGRI SIDOARJO, 2021)
The aim of the study was to improve the students’ ability in speaking skill by applying Classroom Action Research (CAR) using a collaborative design. The procedures of the study consist of five steps, namely: preliminary study, planning, implementing the plan, observing the action, and reflecting on the action. The study was conducted in two cycles. The study was conducted at SMPN 35 Surabaya. It was applied in the first semester of the academic year 2020/2021. The subjects of the study were the ninth-grade students comprising 41 students. The data of the study were obtained from the following research instrument: observation and test. The improvement was indicated by the increasing of the students’ mean scores of speaking skill test administered at the end of students’ means score in preliminary study was indicated by the increasing of the students’ means score in preliminary study was 6.95 in the first cycle and 7.21 in the second cycle. Meanwhile, the percentage of increasing was from 46% (first cycle) to 75% (second cycle).